2010
DOI: 10.1021/jp910955r
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State and Local Structure of Ti-Based Additives in the Reactive Hydride Composite 2LiBH4 + MgH2

Abstract: Nowadays, the technological utilization of reactive hydride composites (RHC) as hydrogen storage materials is limited by their reaction kinetics. However, addition of transition-metal-based additives, for instance titanium isopropoxide (Ti-iso), to the 2LiBH4+MgH2 system, results in a significant improvement of sorption kinetics. In this work, the evolution of chemical state and local structure of the Ti-based additive has been investigated by means of X-ray absorption (XAS) and photoemission (XPS) spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 32 publications
12
73
0
Order By: Relevance
“…In previous works [20][21][22] it has been also demonstrated that the Ti based additive is present after ball milling as Ti oxide like species whereas upon cycling the additive migrates to the bulk as a mix of TiB 2 and Ti 2 O 3 species. It has been pointed out that the Ti-boride active phase may play its main role at the LiBH 4 -Mg interface in the bulk where it is promoting the heterogeneous nucleation of the MgB 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous works [20][21][22] it has been also demonstrated that the Ti based additive is present after ball milling as Ti oxide like species whereas upon cycling the additive migrates to the bulk as a mix of TiB 2 and Ti 2 O 3 species. It has been pointed out that the Ti-boride active phase may play its main role at the LiBH 4 -Mg interface in the bulk where it is promoting the heterogeneous nucleation of the MgB 2 .…”
Section: Discussionmentioning
confidence: 99%
“…These active species have been unequivocally detected by previous XAS and TEM studies. [19][20][21] Figure 6 also shows the Ti 2p photoelectron peaks for the same samples after one hour Ar + sputtering treatment. The removal of material, by long time sputtering, shows the presence of the Ti phases in the cycled samples in the subsurface region.…”
Section: B X-ray Photoelectron Analysismentioning
confidence: 99%
See 3 more Smart Citations